2015
DOI: 10.1039/c4cc08609k
|View full text |Cite
|
Sign up to set email alerts
|

One-step functionalization of zwitterionic poly[(3-(methacryloylamino)propyl)dimethyl(3-sulfopropyl)ammonium hydroxide] surfaces by metal–polyphenol coating

Abstract: The non-biofouling properties of a zwitterionic sulfobetaine polymer surface were easily made attractive to bioentities (e.g., proteins and cells) by metal-polyphenol coating, and spatio-selective functionalization of the zwitterionic polymer surface was achieved by using a soft lithographic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Additionally, the infrared absorption peak at 1352 cm −1 for NiAl-LDHs and LDHs@TA-Ti was attributed to the vibrations of CO 3 2 ⁻ in the interlayer [ 19 ]. Compared with NiAl-LDHs, LDHs@TA-Ti shows additional peaks at 1709, 1496, 1320 and 1197 cm −1 , which corresponded to C=O (ester groups), C–O, aromatic C=C and phenolic hydroxyl in TA, respectively [ 20 , 21 , 22 ]. In addition, the bands recorded below 700 cm −1 were attributed to metal-oxygen vibration in NiAl-LDHs [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the infrared absorption peak at 1352 cm −1 for NiAl-LDHs and LDHs@TA-Ti was attributed to the vibrations of CO 3 2 ⁻ in the interlayer [ 19 ]. Compared with NiAl-LDHs, LDHs@TA-Ti shows additional peaks at 1709, 1496, 1320 and 1197 cm −1 , which corresponded to C=O (ester groups), C–O, aromatic C=C and phenolic hydroxyl in TA, respectively [ 20 , 21 , 22 ]. In addition, the bands recorded below 700 cm −1 were attributed to metal-oxygen vibration in NiAl-LDHs [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FT‐IR spectra of CMC showed that peak at 1585 cm −1 due to the stretching vibrations of carbonyl (CO), peak at 1410 cm −1 due to the characteristic peak of COO on CMC, and the peak at 1317 cm −1 was corresponding to CO stretching . Furthermore, peaks originating from ring stretching in benzene from 1500 to 1600 cm −1 were observed owing to the benzene moieties of TA . However, in the hydrogel formed from CMC and TA, a decrease in the peaks for ring stretching in benzene and a decrease in OH and/or NH stretch vibration peaks were detected obviously.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the antifouling performance of PMPDSAH coated surfaces is outperforming that of the PEG surfaces [ 137 ]. Moreover, this polymer can be functionalized by a 1.9 nm thick metal–polyphenol coating to make it attractive to proteins and cells [ 138 ]. This is particularly important when targeting the spatio-selective functionalization of a specific surface.…”
Section: Recent Antimicrobial Structures Assembled From Polymers On Surfacesmentioning
confidence: 99%